Analytical modeling of shear behaviors of rockbolts perpendicular to joints - Ma, Shuqi (2020)
Rockbolts have been used to minimize the deformation of underground excavations where the surrounding rock masses contain weak planes such as fractures, joints or faults. Rockbolts installed across rock joints are able to resist the opening and shearing movements of rock joints. One of the rockbolt failure modes encountered in the field is caused by the excessive shear loads. A simple analytical model based on the Beam on Elastic Foundation (BEM) method is proposed in this study to predict the shear responses of a bolt installed perpendicularly to rock joint. The shear load-displacement curve of a double shear test can be divided into three stages: the elastic stage, the elasto-plastic stage and the plastic stage. The foundation stiffness for each respective stage are varied with the curvature influencing zone Lc. The pretension effects are taken into account in the proposed analytical model. The model agrees well with the experimental shear tests, suggesting that the analytical model has the capability to predict the shear load-displacement curve of bolts crossing rock joints.